Membangun Layanan Telepon Voice Over Internet Protocol Dengan Menggunakan Server Trixbox Di Smk Pemda Rantauprapat - Pratama, Zakaria; Juledi, Angga Putra; Muti Ah, Rahma (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2023)
SMK Swasta Pemda Rantauprapat is one of the schools in Labuhanbatu Regency which is one of the oldest vocational schools in Labuhanbatu Regency, where communication has been carried out using paid telephones so that it becomes an additional cost that burdens the school's finances. Along with the rapid development of technology, it has resulted in free telephone services, one of which is VoIP (Voice Over Internet Protocol) technology with VoIP technology which can be used as the right solution to solve this problem. In building a VoIP system, a voip server is needed, namely Trixbox. Trixbox is a Voip Server built on the Linux CentosOs operating system which is open source so it can be developed. Communication using VoIP technology only requires a computer/leptop, microphone, speakers, smartphone and a LAN network using both wired and wireless. With VoIP technology in schools, school principals, vice principals, heads of departments and teachers can communicate without incurring telephone costs.